Answer:
htgjyk
Step-by-step explanation:
Answer:
$45
Step-by-step explanation:
1.54(x) = 69.3
Divide both sides by 1.54
x = 45
Answer:
slope is -3
Step-by-step explanation:
change in y over change in x is -3/1
7 ounces / 6 steaks = 12 ounces per steak
6 steaks / 72 ounces = 1/12 steak per ounce
Answer:
x = 1
Step-by-step explanation:
Well the first step is to apply the distributive property:
4(3x - 1) is equal to (12x - 4). You DISTRIBUTE a '4' to what is inside the parentheses.
And btw, to make it easier, you can make 9 - x so that x is first. For example, (-x + 9). They're both the same thing, just written differently.
Your new equation is 12x - 4 = -x + 9. You want to now solve the equation.
Add the (-x) to both sides. It cancels out on the right side and you add it to 12x on the left side.
[If there's no number in front of a variable, you can always just put 1 in order to make it easier]
12x + 1x = 13x. Your new equation is 13x - 4 = 9. This should look very familiar. You simply add 4 to both sides. 9 + 4 = 13
Finally, 13x = 13. Divide 13 ÷ 13 to get 1.
x = 1